Fisherman Hope Post-Disaster Earthquake And Tsunami; Case Study of Sirenja District Donggala - Fery Fery; Ahmad Yani (Universitas Muhammadiyah Palu, 2020)
This research aims to determine the expectation of fishers after natural disasters in the form of earthquakes and tsunami in the Sirenja district of Donggala. The theory used is the theory of hope or expectation that Victor H. Vroom ever expressed. In this theory, it is stated that the power that motivates a person to work actively in working on his work depends on the mutual relationship between what is desirable and necessary for the outcome of the work. The method used is qualitative with five informants prescribed in purposive sampling. Data collection through observation and interviews, which are then analyzed using interactive model methods. The results show that there is a force that motivates fishers to work enterprising again. However, they still depend on the help of both government assistance and the assistance of the Sewasta, such as the Muhammadiyah Disaster Management Center (MDMC) that has been down in the Sirenja district. The fishermen also have expectations to restore their lives like before the earthquake and Tsunami disaster. And the fishermen society desperately wants to go back to the sea; of course, they need some help in the form of capture equipment, such as boats, nets, and machinery, and fishing rods